Is India on a path to reduce the tobacco industry’s influence in tobacco control? Insights from the Global Tobacco Industry Interference Index (2019–2023) - Goel, Sonu; Walia, Diksha; Bhojani, Upendra; Bhatnagar, Nandita; Chopra, Mrinalima (Frontiers in Public Health, 2024)
The tobacco industry (TI), driven by profit motives, consistently conceals health risks through deceptive strategies, notably in countries like India. These tactics create vulnerabilities hindering effective tobacco control measures and enabling the TI to exploit legal gaps.Understanding these TI strategies is essential for policy makers to take appropriate preventive and corrective measures in order to limit Tobacco Industry Interference (TII) in policy making.The study aims at understanding the trend of TII in India between 2019-2023. The secondary data from Global Tobacco Industry Interference report, consisting of seven major domains of TII index viz. policy participation, Corporate Social Responsibility (CSR) activities, industry benefits, unnecessary interaction, transparency, conflict of interest, and preventive measures, was retrieved. A composite score was obtained after adding scores of different domains, for each year. The study's findings demonstrated an initial improvement in India's implementation of WHO FCTC article 5.3, as evidenced by a decreasing score between 2019 and 2021.However, this trend halted in 2023, with data showing a slight increase in the score. When compared with other Asian countries, India show marginal improvement in score than Cambodia, China, Indonesia, Lao PDR, Malaysia, Myanmar, Nepal, Philippines, Thailand and south Korea. Some of the countries in the region including India, Pakistan, Bangladesh, Sri Lanka, Myanmar, Brunei, China and Vietnam experienced a decline in TII. There has been rise in CSR activities, forms of un-necessary interactions of TII with policy makers and participation in policy development; however, improvements are observed in providing benefits to tobacco industry, conflict of interest, and preventive measures. In order to fortify the regulatory framework, it is imperative to create awareness among stakeholders on conflict of interest, denormalize Corporate Social Responsibility (CSR) initiatives by the tobacco industry, provision of a watchdog for TII in the country and 'whole of government' approach in implementation of FCTC Article 5.3.